Commonly Used Wind Generator Systems: A Comparison Note - Prashanth N.A; P Sujatha (Institute of Advanced Engineering and Science, 2017)
Amongst all renewable energy generation sources, wind power exhibits fastest growth rate. The increasing number of wind farm installations worldwide demand low maintenance, cost and failure rates with high efficiency. Determining the optimal drive train configuration amongst various configurations available for wind turbines is a challenge. In this paper commonly used, doubly fed induction generator with single stage gear box (GDFIG), doubly fed induction generator with multi stage gear box (DFIG) and the direct-drive permanent-magnet generator (DDPMG) are compared. Modelling of wind turbine with efficiency computations is presented. Considering common wind turbine parameters, performance of GDFIG, DFIG and DDPMG is compared through an experimental study. Considering a reference 5 MW variable speed wind turbine, efficiency of DDPMG is 96% when compared to 93.58%, 93.12% for DFIG and GDFIG. The experimental results presented prove that the DDPMG is a preferable solution considering low cost and high efficiency.